Leadership Determination and Training Effectiveness on Employee Performance Through Work Motivation Mediation - Maula Zuama; I Ketut R Sudiarditha; Christian Wiradedni Wolor (AIBPM Publisher, 2023)
This study analyses the effect of leadership and training on employee performance by mediating work motivation. This research was conducted in January - October 2022. This study uses a quantitative approach; the sample; chelation in this study was 120 employees of the Directorate General of Islamic Education, with sampling using random sampling techniques. The data obtained through the questionnaire was then managed and coded using Microsoft Excell. Then the data is processed with Structural Equation Modeling (SEM), which is assisted using the Smart-PLS 3.0 analysis program and SPSS by conducting validity and reliability tests. To get the conclusion that there is a positive influence of leadership on employee performance, leadership on work motivation, training effectiveness on work motivation, training effectiveness on employee performance, work motivation on employee performance, leadership on employee performance through the mediation of work motivation and performance effectiveness on employee performance through the mediation of work motivation.